Accommodating Learners With Dyslexia in English Language Teaching in Sri Lanka: Teachers' Knowledge, Attitudes, and Challenges. Issue 3 (28th March 2019) - Indrarathne, Bimali
Abstract : It is estimated that 10% of the world's population has dyslexia or related learning difficulties, and it is therefore vital for language teachers to have a thorough understanding of such difficulties and of inclusive teaching techniques. It is believed that teacher training can increase teachers' knowledge of dyslexia and inclusion, inculcate positive attitudes among them on inclusion, and increase their self‐efficacy beliefs. The study discussed in this article analysed a teacher training programme aimed at a group of English language teaching professionals in Sri Lanka to determine if it could attain these achievements. The study also examined the challenges that teachers would face in introducing inclusive practices into their context. A questionnaire and interview data revealed that the teacher training programme was able to change teachers' negative attitudes towards dyslexia, increase their knowledge of dyslexia and inclusive practices, and increase their readiness to implement inclusive classroom techniques. The findings also revealed that institutional barriers such as a rigid examination system and lack of flexibility in the curriculum may hinder how inclusive practices are implemented. In addition, negative sociocultural ideology and some practical classroom problems may affect implementation. Abstract :